(untitled) (Bangladesh Journal of Nuclear Medicine, 2019)
Objective: Multifocal skeletal tuberculosis is a rare condition in immunocompetent patient even in a tuberculosis endemic area. Diagnosis of such atypical cases is challenging to the physicians and treatment is delayed in majority of cases. The objective of this case report was to present a patient with tuberculosis with skeletal lesions. Case report: A case of 60 years male was presented – with bony pain. His 99m Tc methylene diphosphonate (MDP) scan showed multiple foci of increased radiotracer resembling a metastatic bone disease. However, aspiration cytology and biopsy from the focal lesions and subsequent therapeutic response to anti-tubercular treatment indicated that the lesions were from tubercular infection. Conclusion: Multiple bony lesions from tuberculosis may mimic metastatic lesions in bone scan. Bangladesh J. Nuclear Med. 21(2): 118-121, July 2018